Policing in Hong Kong : history and reform / Kam C. Wong, Xavier University, Department of Criminal Justice, Cincinnati, Ohio, USA. - Wong, Kam C. (Boca Raton, FL : CRC Press, 2015)
'The HKP (Hong Kong Police),'Asia's Finest', is a battle-tested professional organisation with strong leadership, competent staff, and deep culture. It is also a continuously learning and reforming agency in pursuit of organisational excellence. Policing in Hong Kong: history and reform is the first and only book on the development of the Hong Kong Police from an inside out and bottom up perspective.'--Back cover.
Part I. Colonial policing with Chinese characteristics -- Study of policing in Hong Kong -- Debating colonial policing -- Assessing colonial policing -- Policing with Hong Kong characteristics -- Part II. Police reform in 1950s -- Police reform literature -- Policing in colonial Hong Kong -- Formation of Hong Kong police in the 1840s -- HKP reform in the 1950s: context and framework -- HKP reform: the 1950s.
Includes bibliographic references and index.
Keywords: Police -- China -- Hong Kong; Police -- China -- Hong Kong -- History; Police regulations -- China -- Hong Kong; Public safety -- China -- Hong Kong